2011
DOI: 10.1021/cg200888n
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Centered Halogen Bonding: A Factor in Recognition Phenomena and Reactivity

Abstract: Because of the anisotropies of their electronic charge distributions, many covalently bound halogen atoms have regions of positive electrostatic potential (positive sigma-holes) on their outer portions. Through these, the halogens can interact attractively with negative sites. It has sometimes been questioned whether fluorine, the least polarizable halogen, can form halogen bonds, especially in solids. Here we present computational and crystallographic evidence demonstrating that it can indeed do so, in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
194
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 231 publications
(198 citation statements)
references
References 75 publications
3
194
0
1
Order By: Relevance
“…It was in fact shown some years ago that carbon [37], nitrogen [36], oxygen [35], and fluorine [32] can all have positive σ-holes if covalently bonded to strongly electron-attracting partners. From this it follows that they can indeed form σ-hole bonds, and this has been demonstrated computationally [31,32,[35][36][37] and to some extent experimentally [41,53,54].…”
Section: The σ-Hole: Halogensmentioning
confidence: 60%
See 1 more Smart Citation
“…It was in fact shown some years ago that carbon [37], nitrogen [36], oxygen [35], and fluorine [32] can all have positive σ-holes if covalently bonded to strongly electron-attracting partners. From this it follows that they can indeed form σ-hole bonds, and this has been demonstrated computationally [31,32,[35][36][37] and to some extent experimentally [41,53,54].…”
Section: The σ-Hole: Halogensmentioning
confidence: 60%
“…Thus it was formerly thought that fluorine does not form halogen bonds. This has been disproved [32,53,54]. It was in fact shown some years ago that carbon [37], nitrogen [36], oxygen [35], and fluorine [32] can all have positive σ-holes if covalently bonded to strongly electron-attracting partners.…”
Section: The σ-Hole: Halogensmentioning
confidence: 99%
“…However, the electrostatic potentials on the bond extensions are negative, although less so than on the lateral sides of the fluorines. On the other hand, fluorine does have a positive σ-hole potential when the remainder of the molecule is very strongly electron-attracting [64][65][66], e.g., in FCN. In (a), the sulfur is in the foreground, with CF2 groups behind it on both sides.…”
Section: Locations and Strengths Of Positive Potentialsmentioning
confidence: 99%
“…[33] Most fluorine compounds have surface electrostatic potentials that are totally negative, but in some cases, such as FOF, F-F, FCN and others, the fluorine compounds have positive regions of electrostatic potential, which allows them to interact attractively with negative sites. [34] Figure 5 showed the computed electrostatic potential of PF 6 . The result showed that some of the fluorine compounds have positive regions of electrostatic potential along the extensions of the P-F bonds.…”
Section: Resultsmentioning
confidence: 99%